Moodle as Virtual Learning Environment in Developing Language Skills, Fostering Metacognitive Awareness and Promoting Learner Autonomy - Gulbinskienė, Dalia; Masoodi, Marjan; Šliogerienė, Jolita (Pedagogika, 2017)
The study evaluates the potentially relative effectiveness of Moodle as one of the virtual learning environments applied to develop English language skills, foster metacognitive awareness and promote learner autonomy in university settings. The respondents from Mykolas Romeris University and Lithuanian University of Educational Sciences were asked to express their attitude towards Moodle learning environment and assess their views on the improvement of language skills as well as fostering their metacognitive awareness and sense of autonomy in English language learning. The object of the research was students’ evaluation of Moodle as an online English language learning environment. The research revealed that students find Moodle platform motivating in the improvement of their language learning skills. It was also established that using Moodle platform helps to develop metacognitive awareness and fosters learner autonomy.